Experimental research into the effect of some operation factors and rock properties on the rate of penetration - Yassien, Mohamed A.; Sayed, Mohamed A.; Boghdady, Gamal Y.; Ali, Mahrous A.M.; Mohamed, Ahmed S. (National Mining University, 2020)
Purpose. The purpose of this research is to investigate the effect of weight on bit (WOB), rotary speed (RPM), and some rock properties on the rate of penetration (ROP). Methods. Four types of rock were collected from different sites in the south of Egypt (Aswan sandstone, Isawya limestone, Assiut limestone, and Minya marble). These tested samples were drilled by diamond core bit using a fixed laboratory diamond drilling machine under conditions (400 and 1200 rpm), and loads from 12 to 220 kg. WOB, ROP, torque (T) and specific energy (SE) were continuously observed during the drilling trials. The effect of these factors on ROP were examined. Water is used as a flushing and cooling medium. Findings. The effect of some operation factors on the penetration rate regarding mineral composition and different rock type was evaluated and the general equation was carried out to predict the suitable operation factor which gives the best penetration Rate. Originality. The effect of some operation factors on the penetration rate regarding mineral composition and different rock type was evaluated and the general equation was carried out to predict the suitable operation factor which gives the best penetration Rate. Practical implications. The Results demonstrated that ROP was inversely proportional to compressive strength (CS), tensile strength (TS), and density. It was also found that Aswan sandstone, Isawya limestone, Assiut limestone, and Minya marble have CS 111.94 MPa, 131.22 MPa, 125.0 MPa, and 502.5 MPa respectively. Was established that ROP was directly proportional to porosity. Increasing ROP in case of Aswan sandstone is associated with increase in porosity – 23.158%, and in case of Assiut limestone and Isawya limestone ROP is also associated with an increase in porosity – 19.9% and 17.93% respectively. Decreasing ROP in case of Minya marble is associated with decrease in porosity – 2.314%. So, we concluded that marble has lower ROP due to its higher CS, TS, and density and lower porosity than other tested rocks.

Мета. Вивчення впливу комплексу основних експлуатаційних параметрів і ряду фізико-механічних властивостей порід на швидкість буріння в умовах різних родовищ Південного Єгипту. Методика. Були відібрані 4 типи порід з різних районів на півдні Єгипту (Асуанської піщаник, вапняк Ісав, Ассіутскій вапняк і мармур Міньї). Експериментальні зразки отримано на стаціонарній лабораторній буровій установці з алмазним долотом при швидкостях обертання 400 і 1200 об/хв та при навантаженнях від 12 до 220 кг. Під час експериментів постійно вимірювалися навантаження на долото, частота обертання, крутний момент на долоті й питома енергія, а також досліджувався вплив цих факторів на швидкість буріння. Як розчин для промивання і охолоджуючий агент використовувалася вода. Результати. Встановлено залежності швидкості буріння від навантаження на долото, питомої енергії та частоти обертання і питомої енергії. Виявлено, що для всіх чотирьох типів породи швидкість буріння збільшується з ростом навантаження на долото, в той час як питома енергія зменшується з ростом швидкості буріння. Розроблено ефективний спосіб прогнозування продуктивності бурової установки. Встановлено, що швидкість буріння обернено пропорційна міцності на стиск, міцності на розтягнення й щільності, а також змінюється прямо пропорційно пористості. Визначено, що менша швидкість буріння мармуру пов’язана з великими значеннями міцності на стиск, розтяг і щільність, а також з меншою пористістю у порівнянні з іншими досліджуваними породами. Наукова новизна. Встановлено нові закономірності взаємозв’язку експлуатаційних параметрів буріння з урахуванням різного типу породи (пісковик, вапняк, мармур) та її мінерального складу, а також обґрунтовано головну умову експлуатаційного фактору, який забезпечує оптимальну швидкість буріння. Практична значимість. Отримані результати дозволяють вибирати оптимальні параметри і режими буріння в процесі розвідки умов залягання родовищ Південного Єгипту, їх мінерального вмісту та стратиграфічних особливостей. Результати будуть корисними для проектних організацій, наукових інститутів з геології й розвідки, а також гірничих підприємств.

Цель. Изучение влияния комплекса основных эксплуатационных параметров и ряда физико-механических свойств пород на скорость бурения в условиях пород различных месторождений Южного Египта. Методика. Были отобраны 4 типа пород из различных районов на юге Египта (Асуанский песчаник, известняк Исавии, Ассиутский известняк и мрамор Миньи). Экспериментальные образцы получены на стационарной лабораторной буровой установке с алмазным долотом при скоростях вращения 400 и 1200 об/мин и при нагрузках от 12 до 220 кг. Во время экспериментов постоянно измерялись нагрузки на долото, частота вращения, крутящий момент на долоте и удельная энергия, а также и исследовалось влияние этих факторов на скорость бурения. В качестве промывочного раствора и охлаждающего агента использовалась вода. Результаты. Установлены зависимости скорости бурения от нагрузки на долото, удельной энергии и частоты вращения и удельной энергии. Выявлено, что для всех четырех типов породы скорость бурения увеличивается с ростом нагрузки на долото, в то время как удельная энергия уменьшается с ростом скорости бурения. Разработан эффективный способ прогнозирования производительности буровой установки. Установлено, что скорость бурения обратно пропорциональна прочности на сжатие, прочности на растяжение и плотности, а также изменяется прямо пропорционально пористости. Определено, что меньшая скорости бурения мрамора связана с большими значениями прочности на сжатие, растяжение и плотности, а также с меньшей пористостью по сравнению с другими исследуемыми породами. Научная новизна. Получены новые закономерности взаимосвязи эксплуатационных параметров бурения с учетом различного типа породы (песчаник, известняк, мрамор) и ее минерального состава, а также обосновано главное условие эксплуатационного фактора, который обеспечивает оптимальную скорость бурения. Практическая значимость. Полученные результаты позволяют выбирать оптимальные параметры и режимы бурения в процессе разведки условий залегания месторождений Южного Египта, их минерального содержание и стратиграфических особенностей. Результаты будут полезными для проектных организаций, научных институтов по геологии и разведке, а также горных предприятий.
Keywords: rate of penetration; weight on bit; rotary speed; specific energy